2013
DOI: 10.1093/humrep/det266
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant LH supplementation to a standard GnRH antagonist protocol in women of 35 years or older undergoing IVF/ICSI: a randomized controlled multicentre study

Abstract: The trial was registered in the Dutch trial register (ISRCTN10841210).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
62
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 22 publications
3
62
2
Order By: Relevance
“…the number of retrieved oocytes in total age group, 9.6 ± 6.7 vs 8.5 ± 5.5, N.S. ), and it is consistent with those two studies [14, 15]. …”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…the number of retrieved oocytes in total age group, 9.6 ± 6.7 vs 8.5 ± 5.5, N.S. ), and it is consistent with those two studies [14, 15]. …”
Section: Discussionsupporting
confidence: 92%
“…Chung et al [14] performed a retrospective study in 141 cases stratified by an age of <40 years and >40 years. In addition, König et al [15] conducted a randomized controlled trial in 253 patients only aged >35 years on LH supplementation. Our study was retrospective but included larger numbers of patients (465 patients) with mean age 38.8 years (29–45 years), which consisted of 72 patients (15 %) in <35 years old and 393 patients (85 %) in ≥35 years old.…”
Section: Discussionmentioning
confidence: 99%
“…This might be expected as there is a general trend for delayed childbearing in Western societies [19], with many couples seeking ART for this reason [20]. However, although a recent study has failed to find differences in outcomes for women ≥35 years treated with or without LH supplementation during COS [21], there are a growing number of studies that have demonstrated a benefit from LH supplementation [5], which may have contributed to older patients being prescribed the 2:1 formulation of follitropin alfa and lutropin alfa and consequently entering this study. For example, in a recent meta-analysis of data from patients aged ≥35 years (7 randomized controlled trials; 902 ART cycles) r-hLH supplementation of r-hFSH for COS resulted in higher implantation (odds ratio [OR]: 1.36; 95% confidence interval [CI]: 1.05, 1.78) and clinical pregnancy (OR: 1.37; 95% CI: 1.03, 1.83) rates than r-hFSH alone [22].…”
Section: Discussionmentioning
confidence: 99%
“…There were no demographic or clinical differences between the groups. They concluded that LH supplementation has no benefit on ongoing pregnancy rates in women of 35 years or older (König et al, 2013). Vuong et al (2015), through a randomized controlled trial evaluated a total of 240 women aged ≥ 35 years undergoing IVF received ovarian stimulation through a GnRH antagonist protocol.…”
Section: Recombinant Lh Administration In Older Assisted Reproductionmentioning
confidence: 99%